Enhanced Flexibility and Stability of Emissive Layer Enable High‐Performance Flexible Light‐Emitting Diodes by Cross‐Linking of Biomass Material. (14th June 2022) - Sun, Siqi; Jia, Pei; Lu, Min; Lu, Po; Gao, Yanbo; Zhong, Yuan; Tang, Chengyuan; Zhang, Yu; Wu, Zhennan; Zhu, Jinyang; Zhang, Yuantao; Yu, William W.; et al.
Abstract: Flexible perovskite light‐emitting diodes (LEDs) have been highly expected to realize advanced wearable optoelectronic applications due to the excellent optoelectronic properties of perovskites. However, the poor water and oxygen stability and limited flexibility of perovskites prevent their commercialization and applications in flexible LEDs. Herein, the low‐cost and green biomass materials‐ethyl cellulose (EC) is added in the CsPbI3 nanocrystals (NCs), acting as a cross‐linker between neighboring halide octahedra through hydrogen bonds and PbO coordination bonds. It reduces the defect densities of NCs, leading to improved photoluminescence quantum yield. Simultaneously, the synergistic effect of efficient defect passivation and hydrophobic ether groups of EC significantly improve the environment stability of NCs. Additionally, the favorable flexibility of EC and cross‐linking between EC and perovskite NCs improve the deformation resistance of the perovskite layer with stable photoluminescence and negligible cracks after repeated bending. Consequently, flexible LEDs based on the EC‐passivated CsPbI3 NCs achieved a record external quantum efficiency of 12.1% and significantly enhanced operational stability. Moreover, the flexible LEDs show small luminance degradation after bending for 1000 cycles at a radius of 3 mm, and still retain high performance even after repeatedly bending at an ultrasmall bending radius of 1 mm. Abstract : Enhanced stability, flexibility, and optoelectronic properties of CsPbI3 nanocrystals (NCs) are obtained with low‐cost and green biomass materials‐ethyl cellulose (EC) additive. High‐performance flexible light‐emitting diodes based on the EC‐treated CsPbI3 NCs are further achieved with a record external quantum efficiency of 12.1%, significantly enhanced operational stability, and improved flexibility, due to the improved deformation resistance of the perovskite layer upon the addition of EC.